Особенности применения вертебральных методик массажа в оздоровительных и профилактических целях = Features of vertebral massage techniques in wellness and prevention - Samosyuk, I. Z.; Gubenko, V. P.; Samosyuk, N. I.; Tkalina, A. V.; Zachatko, T. M.; Fedorov, S. M.; Chuhraeva, E. N.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Samosyuk I. Z., Gubenko V. p., Samosyuk N. I., Tkalina A. V., Zachatko T. M., Fedorov S. M., Chuhraeva E. N., Zukow W. Особенности применения вертебральных методик массажа в оздоровительных и профилактических целях = Features of vertebral massage techniques in wellness and prevention. Journal of Education, Health and Sport. 2015;5(1):171-202. ISSN 2391-8306. DOI: 10.5281/zenodo.14834 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A171-202 https://pbn.nauka.gov.pl/works/533672 http://dx.doi.org/10.5281/zenodo.14834 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015. ОСОБЕННОСТИ ПРИМЕНЕНИЯ ВЕРТЕБРАЛЬНЫХ МЕТОДИК МАССАЖА В ОЗДОРОВИТЕЛЬНЫХ И ПРОФИЛАКТИЧЕСКИХ ЦЕЛЯХ FEATURES OF VERTEBRAL MASSAGE TECHNIQUES IN WELLNESS AND PREVENTION Самосюк И.З., Губенко В.П., Самосюк Н.И., Ткалина А.В., Зачатко Т.М., Федоров С.М., Чухраева Е.Н., Жуков В.А. Samosyuk I. Z., Gubenko V. p., Samosyuk N. I., Tkalina A. V., Zachatko T. M., Fedorov S. M., Chuhraeva E. N., Zukow w. Національна медична академія післядипломної освіти імені П.Л. Шупика, Kyiv, Ukraine Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska National Medical Academy of postgraduate education named after P.L. Shupyk, Kyiv, Ukraine Kazimierz Wielki University, Bydgoszcz, Poland Ключевые слова: позвоночные массажные техники; оздоровительный массаж. keywords: vertebral massage techniques; wellness. резюме Есть средство, которое уже многие века приносит людям пользу, укрепляет их здоровье, поднимает жизненный тонус, делает мышцы сильными и упругими. Одним оно продлевает молодость, другим возвращает бодрость и хорошее самочувствие. Средство это – массаж (Бирюков А.А., 1977). Массаж – это метод дозированного механического воздействия на ткани и органы больного с помощью рук массажиста в виде определенных приемов или специальных аппаратов. Вопросы, связанные с назначением массажа, требуют соблюдения медицинской этики, такта. При назначении массажа врач должен указать, в каком сочетании с другими процедурами следует применять его разновидности, должен постоянно наблюдать за больным, а массажист должен сообщать врачу обо всех отклонениях. Такой подход к применению массажа делает этот метод наиболее эффективным при лечении различных заболеваний и повреждений. abstract There is a tool that brings people for many centuries, strengthens their health benefits, raises a vitality that makes the muscles strong and supple. one it prolongs youth, the other gets the vivacity and good mood. this tool-massage (Biryukov A., 1977). Massage is a method of measured mechanical impact on the patient's tissues and organs through the hands of the masseur in the form of certain techniques or special apparatus. Issues relating to the appointment of massage require adherence to medical ethics, quantum. When a massage therapist should indicate in which combined with other procedures should apply its variety, must constantly monitor the patient and the therapist should inform your doctor about all deviations. Such an approach to the application of massage makes this method is most effective in the treatment of various diseases and injuries.